Synthesis and physical-chemical properties of 3-benzyl-8-(5-mercapto-4-phenyl-[1,2,4]-triazole-3-ylmethylthiomethyl)xanthine and its s-substituted derivatives - K. V. Аleksandrova; A. S. Shkoda; S. V. Levich; M. V. Dyachkov; D. M. Yurchenko (Zaporozhye State Medical University, 2015)
Aim. Currently, researches, devoted to obtain new active compounds, are carried out among various classes of organic compounds, and combination of several active heterocyclic fragments in one molecule is considered the key way in such researches. Methods and results. For this purpose, we have developed a preparative method of synthesis of 3-benzyl-8-(5-mercapto-4-phenyl-[1,2,4]-triazole-3-ylmethylthiomethyl)xanthine and its S-substituted derivatives. On example of propyl ester of [5-(3-benzylxanthinyl-8-methylthiomethyl)-4-phenyl-[1,2,4]triazole-3-yl]thioacetic acid the possibility of further functionalization of triazolylmethylthiomethylxanthines has been shown. Conclusion. The structures and identity of all synthesized compounds have been proved by elemental analysis, IR-, 1H NMR-spectroscopy, mass-spectrometry and by thin layer chromatography.